2022
DOI: 10.1007/s42000-022-00400-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between medication adherence and health-related quality of life of patients with diabetes

Abstract: Purpose The purpose was to evaluate the association between medication adherence and health-related quality of life (HRQoL) of patients with diabetes. Methods In this cross-sectional study, a total of 518 patients were recruited from the outpatient departments of different general public and private hospitals in Greece during the COVID-19 pandemic using a consecutive sampling method. HRQoL was assessed with the EQ-5D-5L instrument and medication adherence with the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…In 18 primary studies, gender was determined as a significant predictor of HRQoL. Females were shown to have significantly poorer HRQoL and the most statistically significant in the physical and psychological domain ( Al Hayek et al, 2014 ; Alsayed Hassan et al, 2022 ; Alshayban & Joseph, 2020 ; Barua et al, 2021 ; Bourdel-Marchasson et al, 2013 ; Chantzaras & Yfantopoulos, 2022 ; Chew et al, 2015 ; Gebremedhin et al, 2019 ; Hamady et al, 2022 ; Natarajan & Mokoboto-Zwane, 2022 ; Nguyen et al, 2018 ; Saleh et al, 2015 ; Shamshirgaran et al, 2016 ; Tran Kien et al, 2021 ; Wan et al, 2016 ; Wonde et al, 2022 ; Zare et al, 2020 ) in particular, on the dimensions of physical functioning, emotional role, energy, emotion, social functioning, and pain ( Al Hayek et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 18 primary studies, gender was determined as a significant predictor of HRQoL. Females were shown to have significantly poorer HRQoL and the most statistically significant in the physical and psychological domain ( Al Hayek et al, 2014 ; Alsayed Hassan et al, 2022 ; Alshayban & Joseph, 2020 ; Barua et al, 2021 ; Bourdel-Marchasson et al, 2013 ; Chantzaras & Yfantopoulos, 2022 ; Chew et al, 2015 ; Gebremedhin et al, 2019 ; Hamady et al, 2022 ; Natarajan & Mokoboto-Zwane, 2022 ; Nguyen et al, 2018 ; Saleh et al, 2015 ; Shamshirgaran et al, 2016 ; Tran Kien et al, 2021 ; Wan et al, 2016 ; Wonde et al, 2022 ; Zare et al, 2020 ) in particular, on the dimensions of physical functioning, emotional role, energy, emotion, social functioning, and pain ( Al Hayek et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the factors that affected HRQoL was age. The majority of studies revealed that patients with older age have lower HRQoL ( Alsayed Hassan et al, 2022 ; Bourdel-Marchasson et al, 2013 ; Chantzaras & Yfantopoulos, 2022 ; Gebremariam et al, 2022 ; Kalayou Haftu et al, 2022 ; Kang et al, 2021 ; Saleh et al, 2015 ; Tran Kien et al, 2021 ; Wan et al, 2016 ; Zare et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HRQoL is defined as the impact a disease and its treatment have on a patient’s physical, functional, psychological, social, and financial well-being [ 2 , 3 , 4 ]. In cancer care, there is a growing recognition of the significance of HRQoL, as reduced HRQoL may result in lower treatment adherence [ 5 ] and an increased risk of mortality [ 6 ]. A more comprehensive definition of HRQoL could encompass dispositional optimism, which is a psychological attribute associated with health advantages [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although not a diabetes journal per se, Hormones publishes a fair amount of data and findings on diabetes research. The most recent publication by Chantzaras et al [9] and studies by a number of other authors previously underscore our abiding interest in the causes and pathophysiology, genetics, and treatment, as well as clinical complications of the various types of diabetes. In this issue, there are two excellent studies on BNP levels and erectile dysfunction in type 2 diabetes mellitus [10,11], one focusing on continuous insulin infusion treatment [12], as well as an animal study of diabetic peripheral neuropathy [13].…”
mentioning
confidence: 98%